Effects of Alpha-Lactalbumin or Whey Protein Isolate on Muscle Damage, Muscle Pain, and Mood States Following Prolonged Strenuous Endurance Exercise - Qin, Lu; Wong, Stephen H. S.; Sun, Feng-Hua; Huang, Yu; Sheridan, Sinead; Sit, Cindy H. P. (Frontiers in Physiology, 2017)
This study compared the effect of alpha-lactalbumin and whey protein on muscle damage, muscle pain, and mood states during short term recovery following strenuous prolonged exercise. In a two-stage crossover counterbalanced design, 12 endurance male runners were recruited (age: 30.4 ± 2.8 year, height: 172.7 ± 5.6 cm, body mass: 66.7 ± 6.5 kg, VO2max: 58.0 ± 6.9 ml/kg−/min), ran for 90 min at 70% VO2max, and followed by a 4-h recovery. Two treatments (carbohydrate+alpha-lactalbumin, CA; carbohydrate+whey protein isolate, CW) were applied during the main trials. During the first 2-h of recovery, CHO was served at the rate of 0.66 g/kg/h and PRO at 0.34 g/kg/h every 30 min. Creatine kinase (CK), interleukin-6 (IL-6), salivary cortisol, rating of muscle pain, pressure pain threshold (PPT), and mood states were evaluated before (Pre-ex), immediately (Post-ex0), 2 h (Post-ex2h) and 4 h (Post-ex4h) after exercise. 24 h after exercise (Post-ex24h), CK and IL-6, muscle pain, and PPT were evaluated. Compared with Pre-ex, Post-ex24h CK was higher in both trials of CA (398.16 ± 41.37 vs. 184.77 ± 22.68 IU/L, P = 0.039) and CW (418.17 ± 67.86 vs. 202.41 ± 22.26 IU/L, P = 0.037). IL-6 was also higher than Pre-ex at Post-ex0 and Post-ex2h in trials of CA (Post-ex0 vs. Pre-ex0: 7.87 ± 0.74 vs. 1.69 ± 0.23, P < 0.01; Post-ex2h vs. Pre-ex0: 5.39 ± 0.88 vs. 1.69 ± 0.23, P = 0.02) and CW (Post-ex0 vs. Pre-ex0: 8.63 ± 1.06 vs. 1.59 ± 0.19, P < 0.01; Post-ex2h vs. Pre-ex0: 5.75 ± 1.33 vs. 1.59 ± 0.19, P < 0.01). No difference was found in CK and IL-6 between two trials at all time points (all P > 0.05). Compared with Pre-ex0, salivary cortisol was elevated at Post-ex0 in both trials (CA: 0.96 ± 0.13 vs. 0.41 ± 0.05 ng/ml, P < 0.01; CW: 1.15 ± 0.18 vs. 0.43 ± 0.06 ng/ml, P < 0.01) and was lower at Post-ex24h than Pre-ex in CA trial (0.17 ± 0.02 vs. 0.41 ± 0.05 ng/ml, P < 0.01). Compared with CW, PPT was higher at Post-2h in CA trial (31.55 ± 3.09 vs. 26.99 ± 2.32 N/cm2, P < 0.01). Compared with Post-ex0, feeling of fatigue was lower at Post-ex2h (P = 0.014) and Post-ex4h (P < 0.01) in CA, while it was lower at Post-ex4h (P = 0.038) in CW. Compared with CW, feeling of fatigue was marginally lower in the CA trial at Post-ex2h (P = 0.056). In conclusion, compared with the co-ingestion of CHO and whey PRO isolate, co-ingestion of CHO and alpha-lactalbumin reduced sensitivity to the muscle pain, attenuated feeling of fatigue and was more beneficial to reduce the feeling of fatigue and cortisol responses during 4-h recovery following 90-min running at 70% VO2max.